Experience of Using Remdesivir in Patients with Novel Coronavirus Infection - V. I. Petrov; A. Yu. Ryazanova; N. S. Privaltseva; D. A. Nekrasov (Безопасность и риск фармакотерапии, 2022)
Timely, effective, and safe antiviral therapy in COVID-19 patients reduces complications, disability and mortality rates. The greatest concern with remdesivir is the risk of drug-induced liver injury, including in patients whose liver function is compromised by COVID-19.The aim of the study was to investigate the efficacy and safety of remdesivir in patients with confirmed SARS-CoV-2 infection who had been admitted to an infectious diseases hospital in the Volgograd region in March 2022. Materials and methods: the authors carried out an open, non-randomised, single-arm study using medical records of 234 patients who had been diagnosed with “U07.1 COVID-19, virus identified” and prescribed remdesivir upon admission. The effectiveness of therapy was evaluated using two criteria: the need for oxygen supplementation or ventilatory support, or mortality. The authors conducted the evaluation on days 7, 14, and 28 using the six-point ordinal severity scale by Y. Wang et al. The safety of therapy was assessed on the basis of complaints and changes in laboratory findings.Results: for the patients prescribed remdesivir at admission, the 7-day mortality rate was 3.0%, the 14-day mortality rate was 5.6%, and the 28-day mortality rate was 7.3%. With the exception of a patient with myocardial infarction, all the patients who had been hospitalised with mild COVID-19 and prescribed remdesivir did not require oxygen therapy and/or transfer to intensive care and were discharged following recovery. The patients with moderate to severe COVID-19 had the 14-day mortality rate of 6.4% and the 28-day mortality rate of 8.6%. 17 patients (7.2%) discontinued remdesivir prematurely for various reasons, including adverse drug reactions. Remdesivir therapy of 5-10 days was associated with an increase in ALT activity by 2.7 ± 0.8 times in 15.9% of patients with mild COVID-19, by 3.8 ± 1.8 times in 20.4% of patients with moderately severe COVID-19, and by 4.8 ± 2.7 times in 24% (12/50) of patients with severe COVID-19. In two patients (0.9%), the increase exceeded 10-fold the upper limit of normal.Conclusions: the obtained results support recommending remdesivir to patients with mild, moderate and severe COVID-19, including those with moderately elevated baseline activity of hepatic transaminases.